In Vivo Functional Evaluation of Tissue-Engineered Vascular Grafts Fabricated Using Human Adipose-Derived Stem Cells from High Cardiovascular Risk Populations - Krawiec, Jeffrey T. (Tissue Eng Part A, 2016)
Many preclinical evaluations of autologous small-diameter tissue-engineered vascular grafts (TEVGs) utilize cells from healthy humans or animals. However, these models hold minimal relevance for clinical translation, as the main targeted demographic is patients at high cardiovascular risk such as individuals with diabetes mellitus or the elderly. Stem cells such as adipose-derived mesenchymal stem cells (AD-MSCs) represent a clinically ideal cell type for TEVGs, as these can be easily and plentifully harvested and offer regenerative potential. To understand whether AD-MSCs sourced from diabetic and elderly donors are as effective as those from young nondiabetics (i.e., healthy) in the context of TEVG therapy, we implanted TEVGs constructed with human AD-MSCs from each donor type as an aortic interposition graft in a rat model. The key failure mechanism observed was thrombosis, and this was most prevalent in grafts using cells from diabetic patients. The remainder of the TEVGs was able to generate robust vascular-like tissue consisting of smooth muscle cells, endothelial cells, collagen, and elastin. We further investigated a potential mechanism for the thrombotic failure of AD-MSCs from diabetic donors; we found that these cells have a diminished potential to promote fibrinolysis compared to those from healthy donors. Together, this study served as proof of concept for the development of a TEVG based on human AD-MSCs, illustrated the importance of testing cells from realistic patient populations, and highlighted one possible mechanistic explanation as to the observed thrombotic failure of our diabetic AD-MSC-based TEVGs.